What are the shared decision‐making experiences of adult children in regard to their parent/s' health care in residential aged care facilities?. (24th March 2021) - Monson, Ainslie; Hendricks, Joyce; Sundin, Deborah
Abstract: Aim: This scoping literature review aimed to answer the question: What are the shared decision‐making experiences of adult children in regard to their parent/s' health care in residential aged care facilities? Background: Shared decision‐making has been an important patient‐centred approach to nursing care since the 1990s, yet it is becoming increasingly evident that it is still not the reality in aged care facilities fifty years on. Currently, it is not well understood how adult children participate in shared decision‐making and the types of decisions they are required to make. Design: A review of original research papers using Kable, Pich and Maslin‐Prothero 12‐step systematic approach to documenting a search strategy. Method: The researcher screened 597 articles from four databases, published in the English language, during the period 1985–2019. The researcher used the Mixed Methods Appraisal Tool version 2011 to determine the methodological quality of the included studies. The Joanna Briggs Institute QARI data tool was used to appraise the seven selected articles and thematically analyse findings, respectively. Results: Four themes were highlighted: communication; staffing; being involved; and staff–family relationships. Despite these themes being apparent, families have limited opportunities to participate in shared health decision‐making in regard to their parents' care. Conclusion: The findings from this literature show how shared decision‐making is affected by the RACF environment. There is a need to find out and understand what is important from a family member's point of view to optimise shared decision‐making and nursing care of the family member in residential aged care settings. Relevance to clinical practice: The limited findings specific to the SDM experiences of adult children of parents in RACFs in this review could help staff and RACFs to develop strategies and staff training to encourage and facilitate the implementation of shared health decision‐making with staff and families on older people's care.